Excavation failure due to pipeline damage during shallow tunnelling in soft ground. (February 2015) - Hou, Yanjuan; Fang, Qian; Zhang, Dingli; Wong, Louis Ngai Yuen
Abstract: In urban areas, subway construction inevitably imposes negative impacts on adjacent buried pipelines. During the recent construction of the Beijing subway, several ground failures have occurred due to the pipeline damages induced by tunnel construction. In this paper, a disastrous ground failure of such kind occurred during the Beijing subway Line 10 construction is presented, in which a sinkhole about 20 m long, 14 m wide and 12 m deep formed. Both the tunnel construction and the ground traffic were severely affected. The adopted remedial measures for this failure, including road restoration, dewatering, dredging and tunnel face reinforcement, are systematically illustrated. The probable mechanism of this failure is also analyzed and briefly discussed. The case presented in this paper can serve as a practical reference for the engineers practicing in the similar engineering field.